Pengaruh Likuiditas, Leverage, Intensitas Modal, dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Hadi Cahyadi; Catherine Surya; Henryanto Wijaya; Susanto Salim (Universitas Matana, 2020)
In this study aims to examine the impact of liquidity, leverage, capital intensity, and firm size as moderation variable to tax aggressiveness in listed manufacturing entities in IDX (Indonesian Stock Exchange) period 2015-2018. This study use 65 manufacturing companies as sample in this study and also use multiple regression analysis. Results of this study indicate that liquidity were’nt significant negative to tax aggressiveness, and leverage were significant positive to tax aggressiveness, capital intensity not significant positive to tax aggressiveness, firm size not significant negative to tax aggressiveness, firm size is able to moderate liquidity, leverage, and capital intensity to tax aggressiveness.